Cow's Milk and Allergy - Van Neerven, RJ Joost (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The purpose of this Special Issue "Cow's Milk and Allergy" is to provide an overview of the association of cow's milk with allergy. This topic has two quite different faces. On the one hand, we are all aware of the importance of cow's milk allergy in early life. What is less known is that the consumption of raw, unprocessed milk is associated with a lower incidence of asthma and rhinitis. This Special Issue takes a closer look at all of these aspects of cow's milk and allergy and focus on the following questions: